2011
DOI: 10.4161/cc.10.3.14709
|View full text |Cite
|
Sign up to set email alerts
|

Multiple faces of FoxM1 transcription factor

Abstract: -/-mice exhibit embryonic lethal phenotype due to multiple abnormalities in the liver, heart, lung and blood vessels. FoxM1 levels are dramatically decreased in adult tissues, but FoxM1 expression is re-activated during organ injury and numerous cancers. In this review, we discussed the role of FoxM1 in different cell lineages using recent data from transgenic mouse models with conditional "gain-of-function" and "loss-of-function" of FoxM1, as well as tissue samples from human patients. In addition, we provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
146
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(148 citation statements)
references
References 76 publications
(130 reference statements)
2
146
0
Order By: Relevance
“…Our in vitro and in vivo studies demonstrated that SPDEF inhibits Cdc25b , Cyclin B1 , Cyclin A2 , Plk1 , Cks1 , Aurora B , and Topo 2 alpha mRNAs, all of which are known targets of Foxm1 transcription factor [29]. Since Foxm1 is up-regulated in mouse and human prostate cancers and is required for prostate carcinogenesis [8], [10], we tested whether SPDEF inhibits Foxm1.…”
Section: Resultsmentioning
confidence: 99%
“…Our in vitro and in vivo studies demonstrated that SPDEF inhibits Cdc25b , Cyclin B1 , Cyclin A2 , Plk1 , Cks1 , Aurora B , and Topo 2 alpha mRNAs, all of which are known targets of Foxm1 transcription factor [29]. Since Foxm1 is up-regulated in mouse and human prostate cancers and is required for prostate carcinogenesis [8], [10], we tested whether SPDEF inhibits Foxm1.…”
Section: Resultsmentioning
confidence: 99%
“…It is a key cell-cycle regulator of both the transition from G1 to S phase and the progression to mitosis [14][15][16]. It has been shown to play important roles in regulating the expression of genes involved in cell proliferation, differentiation, and transformation [17]. Increased expression of FoxM1 has been found in several human tumors suggesting a role in human carcinogenesis [13,[18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In adult organs, FOXM1 is mainly expressed in proliferating cells or induced by growth factor release. In this context, it is not surprising that FOXM1 serves as proto-oncogene in most cancers and aberrant expression or mutations constitute the origin of many treatment resistance mechanisms (Kwok et al 2010; Kalin et al 2011; Saba et al 2016). Although FOXM1 is exclusively expressed in dividing cells, its targeting may result in many side effects given its involvement in angiogenesis, cell migration and epithelial–mesenchymal transition (Halasi and Gartel 2013).…”
Section: Introductionmentioning
confidence: 99%